Post operative Anterior Chamber Reaction in Adult Cataract Surgery after Adding Heparin in Irrigating Solution - Qaim Ali Khan, Yasir Iqbal, Sohail Zia (Pakistan Journal of Ophthalmology, 2014)
Purpose: To document the post operative anterior chamber reaction in adult cataract surgery after adding heparin in irrigation solution. Material and Methods: It was a Quasi Experimental Study in which 193 eyes of patients, with ages 50 years to 75 years, were selected by Convenience (Non Probability) sampling technique for cataract surgery in Redo Eye hospital, Rawalpindi from Feb 2011 to Dec 2011. All the cases under went operation by the single surgeon having expertise in the technique of manual sutureless cataract surgery (MSCS). At the beginning of the surgery, 1 ml of heparin sodium (concentration 10 IU/ml) was added to the balanced salt solution to irrigate the anterior chamber during the surgery. All patients were followed on the first post operative day and after one week. At follow up visits, postoperative intraocular cellular reaction based upon modified Hogan’s classification was noted. Results: On the first post operative day, 5.2% of the cases had mild and 1% cases had moderate anterior chamber reaction. The patient were put on the standard topical treatment and on first week follow up the anterior chamber reaction was absent in all of the cases. Conclusion: We found that after adding heparin in the irrigating solution there was mild anterior chamber reaction in 5.2% of our cases and it can play a role to reduce the post operative inflammation in adult cataract surgery. Key Words: Cataract Surgery, Heparin, Anterior Chamber